2018
DOI: 10.1016/j.jcv.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of the Determine HBsAg point-of-care test for diagnosis of hepatitis B virus co-infection among HIV patients in Zambia

Abstract: Background We evaluated the field performance of a rapid point-of-care (POC) test for hepatitis B surface antigen (HBsAg) that could support decentralization and scale-up of hepatitis B virus (HBV) diagnosis in Africa. Objective To determine the field performance of the Determine HBsAg POC test for diagnosis of HBV co-infection among HIV patients in Zambia. Study design Between 2013–2014, we screened HIV-infected adults for HBsAg at two urban clinics in Zambia. A subset were tested with the POC Determine H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Whereas, one step HCV test strip (Nantong Diagnos Technology Co., Ltd., China) was used to detects antibodies against HCV following the instructions of the manufacturer. Samples found positive for HBV infection by one step HBsAg test strip were further screened using qualitative immunoassay Alere Determine TM HBsAg (Alere Inc., Massachusetts, USA) which is more specific but less sensitive than the One Step HBsAg test [23–25]…”
Section: Methodsmentioning
confidence: 99%
“…Whereas, one step HCV test strip (Nantong Diagnos Technology Co., Ltd., China) was used to detects antibodies against HCV following the instructions of the manufacturer. Samples found positive for HBV infection by one step HBsAg test strip were further screened using qualitative immunoassay Alere Determine TM HBsAg (Alere Inc., Massachusetts, USA) which is more specific but less sensitive than the One Step HBsAg test [23–25]…”
Section: Methodsmentioning
confidence: 99%
“…Using a common protocol, we collected information on the following demographic, clinical and behavioural characteristics: age, sex, marital status, education level, CD4 cell count, body mass index, transaminases and ART history. Tobacco consumption was reported as “never smoker” or “current or past smoker.” Viral hepatitis infections were assessed using rapid diagnostic tests: Determine ® (Alere, Waltham, MA, USA) for hepatitis B surface antigen (HBsAg) and Oraquick ® (Orasure, Bethlehem, PA, USA) for anti‐hepatitis C virus (HCV) antibodies, as these tests have shown relatively good diagnostic accuracy, including a validation study performed at our Zambian study site .…”
Section: Methodsmentioning
confidence: 99%
“…Tobacco consumption was reported as "never smoker" or "current or past smoker. " Viral hepatitis infections were assessed using rapid diagnostic tests: Determine â (Alere, Waltham, MA, USA) for hepatitis B surface antigen (HBsAg) and Oraquick â (Orasure, Bethlehem, PA, USA) for anti-hepatitis C virus (HCV) antibodies, as these tests have shown relatively good diagnostic accuracy, including a validation study performed at our Zambian study site [19,20].…”
Section: Study Measurementsmentioning
confidence: 99%
“…A 2017 meta-analysis [ 31 ] including 9 studies with 7730 samples showed a pooled sensitivity of 90.8% and specificity of 99.1% using Determine. Though most studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ] showed high clinical sensitivity of 89–100% in the general population, the reported sensitivity varied widely in HIV-infected populations (56–100%) [ 39 , 40 , 41 , 42 , 43 , 44 ]. The cause of the reported lower sensitivity in HIV-coinfected populations [ 39 , 40 , 43 , 44 ] is unclear, but potential reasons may include the cross reaction of HIV-reverse transcriptase inhibitors and hepatitis B virus, a higher rate of occult hepatitis B infection in early HIV cohorts, a higher reported rate of HBsAg loss in both untreated and treated HIV-infected populations and the use of tenofovir-based HIV regimens that effectively suppress hepatitis B virus DNA levels and a large decline in HBsAg titres [ 31 , 45 , 46 ].…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%